Exploring alternative use of medicinal plants for sustainable weed management - Appiah, K.S.; Mandarin, H.K.; Osivand, A.; Kpabitey, S.; Amoatey, C.A.; Oikawa, Y.; Fujii, Y. (Sustainability (Switzerland), 2017)
This paper presents the first application of ethnobotanical studies to screen for allelopathic species among medicinal plants for sustainable weed management. This study assesses the possible relationship between ethnobotanical indices and allelopathy of medicinal plants. Ethnobotanical data were collected in 2016 by using semi-structured interviews with 140 informants in the Ejisu-Juaben Municipality, Ghana. Data were analysed using statistical tool and ethnobotanical indices including use value (UV), Fidelity Level (FL), Relative Frequency of Citation (RFC). The Sandwich and Dish pack methods were respectively used to evaluate allelopathy through leachates and volatiles of collected samples. Ninety-five species belonging to 43 families are reported in this study, with leaves (52%) cited the most utilised plant part. Cleistopholis patens (UV = 0.54; FL = 90.7%; RFC = 0.37) and Ocimum gratissimum (UV = 0.37; FL = 38.4%; RFC = 0.35) were among the most cited species. Thirty-two species showed inhibition (≥49.3%) by leachates, while twenty-four species were found with potential volatile inhibitory compounds against lettuce radicle growth. There was a significant positive correlation (Pearson) between the UV and RFC of medicinal plants and allelopathy by leaf leachates (r = 0.639 **; p = 0.01 and r = 0.653 **; p = 0.01 respectively). This systematic documentation of medicinal plants in Ejisu-Juaben Municipality shows medicinal plants with ethnomedicinal values and potential allelopathy that can be utilised in sustainable weed control. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: allelopathy; Ejisu-Juaben Municipality; Ethnomedicine; FIDELITY Level (FL); Medicinal plants; Relative Frequency of Citation (RFC); Sustainable weed control; Use value (UV)